Research on effects of pollution in livestock - Swarup, D; Dwivedi, S K (The Indian Journal of Animal Sciences, 2012)
Livestock sharing man’s environment are exposed to an array of toxic pollutants which may be hazardous to their health and production. The health effects of pollution in livestock vary from subtle or chronic intoxication to overt acute toxicities depending on source and kind of pollutant, extent and route of exposure extent and degree of other interacting agents, and species, age, physiology and nutrition of the exposed livestock population. Residue of pollutants in livestock products adversely effect their quality and cause potential threat to public health due to contamination of food chain. In India, problem of pollution is related to poorly planned developmental projects and overuse of natural resources by everincreasing human population. Review of the work done during the 5 decades of post-independence indicated emerging trend of human and livestock health problems due to pollution in the country. Acute and chronic lead toxicosis, fluorosis and pesticide poisoning have been recognised as major health hazards of pollution in livestock with the increasing frequencies in recent past indicating growing threat of pollution to the livestock health. Scientific data also revealed residual effects of pollutants such as toxic heavy metals and pesticides in animal food products. However, as compared to medical data, fewer studies have been conducted to evaluate ill effects of pollution in livestock in the country. There is a need for intensive studies and also to make recommendations as to how best to limit ill effects of pollution in livestock.